THE INFLUENCE OF INCOME, SOCIAL CAPITAL, AND PRODUCTION LEVELS ON THE WELFARE OF MUSLIM FISHERMEN AT PT TIMUR JAYA TELUK NIBUNG - Nina Amelia Mangunsong; Reni Ria Armayani Hasibuan; Aqwa Naser Daula (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The aim of this research is to determine the influence of income, social capital and production levels on the welfare of Muslim fishermen at PT. Timur Jaya Nibung Bay. The type of research used in this research is associative quantitative research with multiple linear regression. The object of this research is Muslim fishermen on the coast of PT Timur Jaya Teluk Nibung with a total of 100 fishermen as respondents. The sampling method uses a simple random sampling technique. The research results show that partially the three variables, namely income, social capital and production levels, together have a positive and significant effect on fishermen's welfare. Simultaneously, the results show that income (), social capital (), and production level () have a significant effect on fishermen's welfare. This research contributes to determine the influence of income, social capital and production levels on the welfare of Muslim fishermen at PT. Timur Jaya Nibung Bay. Not only that, this research can be a reference for further research. Keywords: Income, Social Capital, Production Levels, and Welfare